How Social Media Drives Brand Awareness in Educational Institutions: Evidence from Madrasah Marketing Strategies - Yaqin, Muhammad Ainul; Aini, Rizki Nur (Al-Qalam Institue, 2025)
This study explores the use of social media to enhance brand awareness in madrasah institutions, focusing on MA Nurul Jadid. The research investigates how specific social media platforms, such as Instagram, TikTok, Facebook, and WhatsApp, contribute to increasing the visibility and appeal of madrasah to prospective students and their families. Given the rising importance of digital marketing in education, this study examines how madrasahs can adopt modern strategies to enhance their digital presence. This research used a qualitative approach and a case study methodology; data were collected through in-depth interviews with stakeholders, including social media managers, students, parents, and alumnus, and content analysis of the madrasah's social media activity. The findings suggest that Instagram and TikTok are particularly effective in engaging younger audiences, while Facebook and WhatsApp are crucial for formal communication with parents and alumnus. The study highlights the importance of strategic content creation and consistent engagement in building a strong online presence. These findings contribute to the broader understanding of digital marketing in religious and educational settings. They offer valuable insights for other madrasahs seeking to strengthen their brand image and community engagement through social media.